Challenges in public procurement: an examination of legal implications of non compliance with procurement rules in selected institutions in Morogoro - Kweka,Eveline (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for the award of Master of Laws [LLM] of the Mzumbe University.